A new mutation in TUBB1 associated with thrombocytopenia confirms that C‐terminal part of β1‐tubulin plays a role in microtubule assembly. Issue 6 (30th November 2016) - Fiore, M.; Goulas, C.; Pillois, X.
Abstract :